Mapping innovative corporate environmental responsibility research: a bibliometric analysis - Zhang, Li'ang; Turebekova, B.; Sultan, D. (Journal of Economic Research & Business Administration, 2025)
Climate challenges are rising fast. This makes Corporate Environmental Responsibility (CER) and innovation very important. The intersection of innovation and Corporate Environmental Responsibility (CER) is fast becoming a cornerstone of sustainable development, driven largely by escalating climate pressures. However, the scholarly landscape remains disjointed, often failing to cohesively link technological advancements with financial mechanisms and their actual environmental impacts. To bring order to this fragmented field, we mapped the evolutionary path of innovation-centric CER. Following the PRISMA protocol, we screened 497 peer-reviewed articles from the Web of Science Core Collection (up to April 2025), employing VOSviewer and Biblioshiny for visualization. What stands out is the exponential rise in output, with China functioning as the primary research hub. Thematically, we observed a distinct pivot: the conversation is drifting away from internal metrics like "environmental strategy" and "eco-efficiency," focusing instead on external catalysts such as "green finance," "digital transformation," and "financing constraints." By categorizing the literature into strategic management, sustainable production, and the finance-innovation nexus, this paper offers a consolidated framework. It ultimately lays out a future research agenda to help scholars and practitioners navigate the twin hurdles of digital and green transitions. Key words: Corporate Environmental Responsibility, Innovative Approaches, Bibliometric Analysis, Sustainability Strategies.